Training Of Business Analysis Using SWOT Method in Homestay “Omahe Wong Di Ino” Bantul Yogyakarta - Rinawati Zailani; Choirun Nisaa; Galih Sumarah Erilantu (Jurnal Pengabdian Masyarakat Nusantara, 2023)
In a simple sense, a homestay is a whole house that is rented out to visitors to rest and with facilities like at home. The COVID-19 pandemic has brought businesses down. After the pandemic, business owners are trying to get back up to continue their business. One of the businesses that continues to try to rise after the pandemic is the homestay business "Omahe Wong di Ino" in Bantul Regency, Yogyakarta Province. The business owner and the STIKIP Catur Sakti community service team conducted a business analysis using the SWOT method (Strengths, Weaknesses, Opportunities, and Threats analysis). Owners practice to identify internal and external factors, then they are calculated based on their ratings and weights. The results of the SWOT analysis show that the homestay business "Omahe Wong di Ino" is in a prime company that has great strengths and opportunities. This gives an overview of the strategy that will be carried out by the company. Based on the analysis, the company's strategy is to carry out a growth and expansion strategy by adding homestay buildings for children's education facilities and can accommodate more guests.